Immune reactivity and host modulatory roles of two novel Haemonchus contortus cathepsin B-like proteases - Mariam Bakshi (BMC, 2021)
Abstract Background Haemonchus contortus is a blood-feeding, gastrointestinal nematode (GIN) that causes significant economic losses to the small ruminant industry worldwide. Despite extensive efforts, our understanding of the molecular mechanisms used by GIN to evade host immune responses is limited. Cathepsin B-like proteins (CBPs) are members of the cysteine protease family and are involved in parasite invasion and thus provide viable vaccine candidates. Methods In silico comparative analysis was used to identify conserved proteins among a subset of clade V parasitic nematodes with emphasis on blood-feeding worms, among which CBPs appeared prominently. We identified and characterized two novel CBPs designated Hc-CBP-1 and Hc-CBP-2. Rabbit anti-recombinant (r) Hc-CBP-1 and rHc-CBP-2 were used to detect the presence of native proteins in the excretory secretory products (ESP) and in worm tissues of adult H. contortus. Peptide arrays of rHc-CBP-1 and rHc-CBP-2 were screened with the homologous and heterologous anti-sera and with sera from dexamethasone-treated (Dex+) and non-treated (Dex−) H. contortus-infected animals to identify key immunogenic peptides. Gene transcription of Hc-cbp-1 and Hc-cbp-2 was also performed on H. contortus-infected animals treated with Dex+. Finally, the mature recombinant proteins were used to assess their abilities to modulate cell functions. Results Immunohistochemistry showed that both Hc-CBP-1 and Hc-CBP-2 are present on the brush borders of the intestine; Hc-CBP-2 was also present in the hypodermis of the body wall. Peptide displays screened with rabbit anti-rHc-CBP-1 and anti-rHc-CBP-2 revealed regions within the proteins where dominant and overlapping epitopes prevailed. ELISA results were consistent with only Hc-CBP-1 being present in H. contortus adult ESPs. H. contortus from Dex+ animals exhibited a threefold increase in Hc-cbp-2 transcript while Hc-cbp-1 expression did not change. In contrast, comparisons of immunoreactivities of rHc-CBP-1 and rHc-CBP-2 peptide arrays to sera from Dex+ and Dex− animals primarily showed changes in Hc-CBP-1 binding. Lastly, rHc-CBP-1 suppressed mRNA expression of bovine peripheral blood mononuclear cell cytokines/activation markers, including TNFα, IL-1, IL-6 and CD86. Conclusions These results suggest that as secreted and cryptic proteins, respectively, Hc-CBP-1 and Hc-CBP-2 influence cellular and immunological activities that have interesting dynamics during infection and may provide viable immune-related targets for attenuating H. contortus infectivity. Graphic Abstract